answersLogoWhite

0

Still curious? Ask our experts.

Chat with our AI personalities

ReneRene
Change my mind. I dare you.
Chat with Rene
TaigaTaiga
Every great hero faces trials, and you—yes, YOU—are no exception!
Chat with Taiga
JudyJudy
Simplicity is my specialty.
Chat with Judy

Add your answer:

Earn +20 pts
Q: If a 2 and b 3 find the value of 4a - 2b?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Math & Arithmetic

What are the values of a and b if 6 3 is the midpoint of the line joining 2a comma 2a-b to a-2b comma 4a plus 3b?

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3


Find the additive inverse of 5a2-4a?

4a - 5a^2


If a 4 and b 2 find the value of 7a and minus 2b plus 1.?

It is: (7*4)-(2*2)+1 = 25


GIven Tx equals ax2 plus bx plus c find a b and c if T0 equals -4 T1 equals -2 and T2 equals 6?

T(x) = ax^2 + bx + cT(0) = -4T(1) = -2T(2) = 6Solution:Since T(0) = -4, then c = -4.So, when x = 1, we have:-2 = a(1)^2 + b(1) - 4-2 = a + b - 4-2 + 4 = a + b - 4 + 42 = a + b2 - a = a - a + b2 - a = bWhen x = 2, we have:6 = a(2)^2 + b(2) - 46 = 4a + 2b - 46 + 4 = 4a + 2b - 4 + 410 = 4a + 2b10/2 = 4a/2 + 2b/25 = 2a + b5 - 2a = 2a - 2a + b5 - 2a = b2 - a = 5 - 2a2 - 2 - a + 2a = 5 - 2 - 2a + 2aa = 32 - a = b2 - 3 = b-1 = bThus, a = 3, b = -1, and c = -4.Check:


How do you find the value of c that makes each trinomial a perfect square?

The answer will depend on what c is!If the trinomial is ax^2 + bx + c then the required value of c is (b^2)/(4a)